1988
DOI: 10.1149/1.2095790
|View full text |Cite
|
Sign up to set email alerts
|

Change of Pt Distribution in the Active Components of Phosphoric Acid Fuel Cell

Abstract: Several postmortem analyses were conducted to investigate the change of Pt distribution in the active components in a phosphoric acid fuel cell (PAFC) during a long‐term operation. Quantitative analysis of an electron probe microanalyzer (EPMA) indicates not only the loss of Pt in a cathode but also Pt migration to an anode during operation and identifies the Pt in a matrix. It was found that the behavior of Pt during cell operation is associated with operation mode and presumably subsequent singular distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 0 publications
8
64
0
Order By: Relevance
“…Figure 3b shows the results for another para-PBI membrane fuel cell test at 160 C. There were also some unintended facility events and one of them at 537 h caused a sharp increase in PA loss from the cathode. The voltage degradation rate over 2,500 h was 4.9 lV h -1 and the PA loss rate from the cathode ) was significantly higher than observed in the test at 160 C, and it could be due to many factors such as Pt dissolution [20], Pt agglomeration [21] and carbon support corrosion [22,23] ) was lower than that of para-PBI membrane fuel cell (45 lV h -1 ) at 80 C which may be due to more stable instrument operation. Figure 4b shows long-term operation of 2OH-PBI membrane fuel cell operated at 160 C. The voltage degradation rate at 160 C was 5.8 lV h -1 , which is similar to values reported for the fuel cells with commercial PA doped-PBI membrane (5 lV h -1 operated at 0.2 A cm -2 , 160 C for 6,300 h) [13] and similar to our work in this study for para-PBI at 160 C. Although the voltage degradation rate at 160 C was lower than that at 80 C, the PA loss rate at 160 C (7.1 ng cm -2 h -1 from the cathode) was similar to the value at 80 C (7.6 ng cm -2 h -1 from the cathode).…”
Section: Steady-state Long-term Operation Testsmentioning
confidence: 58%
“…Figure 3b shows the results for another para-PBI membrane fuel cell test at 160 C. There were also some unintended facility events and one of them at 537 h caused a sharp increase in PA loss from the cathode. The voltage degradation rate over 2,500 h was 4.9 lV h -1 and the PA loss rate from the cathode ) was significantly higher than observed in the test at 160 C, and it could be due to many factors such as Pt dissolution [20], Pt agglomeration [21] and carbon support corrosion [22,23] ) was lower than that of para-PBI membrane fuel cell (45 lV h -1 ) at 80 C which may be due to more stable instrument operation. Figure 4b shows long-term operation of 2OH-PBI membrane fuel cell operated at 160 C. The voltage degradation rate at 160 C was 5.8 lV h -1 , which is similar to values reported for the fuel cells with commercial PA doped-PBI membrane (5 lV h -1 operated at 0.2 A cm -2 , 160 C for 6,300 h) [13] and similar to our work in this study for para-PBI at 160 C. Although the voltage degradation rate at 160 C was lower than that at 80 C, the PA loss rate at 160 C (7.1 ng cm -2 h -1 from the cathode) was similar to the value at 80 C (7.6 ng cm -2 h -1 from the cathode).…”
Section: Steady-state Long-term Operation Testsmentioning
confidence: 58%
“…Moreover, dissolved platinum ions can migrate into the electrolyte membrane. To our knowledge, the presence of platinum in the membrane has first been observed by Aragane et al [15], and the formation of precipitations was studied in more detail in follow up publications [16][17][18][19][20] by several authors. In addition to the loss of electrochemically active catalyst also the resistance of the MEA is likely to be affected by the formation of precipitates in the membrane [20].…”
Section: Introductionmentioning
confidence: 88%
“…A quite frequent observance is a Pt band at a certain distance from the cathode [10,[31][32][33][110][111][112]. In the case of PAFC, Pt was able to move to the anode and deposit there [70]. It was found that in PEMFC the position of this band depends on the H 2 and O 2 partial gas pressures, with the band moving towards the anode upon a reduction of the H 2 partial pressure or an increase in the O 2 partial pressure [31,33,111].…”
Section: Reviewmentioning
confidence: 99%